2011
DOI: 10.1007/s11571-011-9175-8
|View full text |Cite
|
Sign up to set email alerts
|

More discussions for granger causality and new causality measures

Abstract: Granger causality (GC) has been widely applied in economics and neuroscience to reveal causality influence of time series. In our previous paper (Hu et al., in IEEE Trans on Neural Netw, 22(6), pp. 829-844, 2011), we proposed new causalities in time and frequency domains and particularly focused on new causality in frequency domain by pointing out the shortcomings/limitations of GC or Granger-alike causality metrics and the advantages of new causality. In this paper we continue our previous discussions and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…When applying the core pairs for classification of CS+ and CS− stimuli, NC appears to be a more robust method with respect to extracting common features expressed at the inter-individual level. Hence, our study supports earlier reports which point out advantages of NC over GC in the analysis of neuronal data based on human EEG (Hu et al, 2011(Hu et al, , 2012(Hu et al, , 2015, and extends these findings to ECoG recordings in small rodents.…”
Section: Significance Of the Experimental Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…When applying the core pairs for classification of CS+ and CS− stimuli, NC appears to be a more robust method with respect to extracting common features expressed at the inter-individual level. Hence, our study supports earlier reports which point out advantages of NC over GC in the analysis of neuronal data based on human EEG (Hu et al, 2011(Hu et al, , 2012(Hu et al, , 2015, and extends these findings to ECoG recordings in small rodents.…”
Section: Significance Of the Experimental Findingssupporting
confidence: 92%
“…Granger Causality has been widely applied to identify the directional influence of system components in many different fields, including neuroscience (e.g., Ding et al, 2006;Wang et al, 2008;Bressler and Seth, 2011;Gao et al, 2011;Ge et al, 2012). In addition to GC, we use New Causality (NC) proposed by Hu et al (2011Hu et al ( , 2012. New Causality generalizes the concept of GC, such that it considers the proportion that X 1 occupies among all contributions to predict X 2 .…”
Section: Metrics For Causality Analysis Of Gerbil Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We used an algorithm in ML that could identify causal effects between the variables. Hu et al ( 2012 ) recommend a D2C algorithm on proportion-based causality using the Oryx 2.0.8 protocol in Apache. However, since an algorithm in ML needs many variables (remembering that the data are not interpreted as a time series), we completed mathematical transformations.…”
Section: Methodsmentioning
confidence: 99%
“…By reviewing related literatures, it can be found that one of the most popular definitions for causality, which falls within modeling class of effective connectivity is GC. It was first introduced by Weiner in 1956 and later formalized by Granger in form of linear regression method in 1969 (Hu et al, 2012 ). GC can be simply defined as follows:…”
Section: Granger Causalitymentioning
confidence: 99%